Best Answer

2x / (y-2) + 2x / (2-y)

First get a common denominator: (y-2) (2-y)

Then you have:

2x(2-y) / (y-2)(2-y) + 2x(y-2) / (y-2)(2-y), summing and simplifying, you get:

(4x-4) / (y-2)(2-y)

Q: What is the sum of 2x divided by y-2 and 2x divided by 2-y?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68

5

Y1=2x^(2/3)+√(20-x²)-3 Y2=2x^(2/3)-√(20-x²)-3

EQ1 x+y=8 EQ2 x2+y2=34 EQ1 x=8-y EQ1 and EQ2 combined gives (8-y)2+y2=34 simplify 64 -16y +y2+y2=34 simplify 2y2-16y+30=0 solve for -16y (2y-?)(y-!)=0 EQA EQ3 -2y!-y?=-16y simplify EQ3 2!+? =16 EQ4 ?!=30 EQ3 ?=16-2! Combined EQ3 and EQ4 gives (16-2!)!=30 simplify 8!-!2=15 Method of exhaustion 8!-!2 when !=0 -> 0 !=2 ->12 !=3->15 !=3 into EQ3 gives ?=16-2! gives ?=10 substitute into EQA gives (2y-10)(y-3)=0 solving gives y=5 or 3 solving for EQ1 x+y=8 then x=3 or 5 solving for EQ2 x2+y2=34 gives 9+25 for either combination so the larger number is 5

Here it is: Y1=2x^(2/3)+√(20-x²)-3 Y2=2x^(2/3)-√(20-x²)-3

Related questions

0.5(x - y)(2x + 2y - 3)

y2x is an expression, which cannot be graphed because we don't know what it equals. y = 2x, y2 = x, and 2y (or y2) = x are all things that could actually be graphed.

What do you want to convert it to? x2 + y2 = 2x If you want to solve for y: x2 + y2 = 2x ∴ y2 = 2x - x2 ∴ y = (2x - x2)1/2 If you want to solve for x: x2 + y2 = 2x ∴ x2 - 2x = -y2 ∴ x2 - 2x + 1 = 1 - y2 ∴ (x - 1)2 = 1 - y2 ∴ x - 1 = ±(1 - y2)1/2 ∴ x = 1 ± (1 - y2)1/2

-2

4x2-y2 = (2x-y)(2x+y)

No. It's a trinomial.'tri' means 'three' termsThe three terms are [ y2 ], [ 2y ], and [ 1 ].

x+y=2x-y=26x=2-yx=26+y2-y=26+y-24=2y-12=yx+(-12)=2x=14You can verify this by plugging -12 and 2 into the original equations.14+(-12)=214-(-12)=26

Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68Assuming the equation is x2 - y2 - 6x - 2y = 60this is equivalent tox2 - 6x + 9 - y2 - 2y - 1 = 60 + 9 - 1= (x - 3)2 - (y + 1)2 = 68

y2 - 2y - 8 = (y - 4)(y + 2) = 0; whence, y = 4 or -2.

x+2y = 30 => x= 30-2y x2+y2 =900 (30-2y)2+y2 = 900 (30-2y)(30-2y)+y2 = 900 900-60y-60y+4y2+y2 = 900 5y2-120y = 0 y(5y-120) = 0 y = 0 or y= 24 Substitute the value of y into the original equations to find the value of x: Therefore: x = -18 and y = 24 Check: -18+48 = 30 and (-18)2+242 = 900

If that's + 2y, the answer is (y + 4)(y - 2)

no